Development of an Instrument to Measure Problem Solving and Numeracy Literacy Based on Ethnomathematics - Hanuri Sakarti; Dian Rahmawati (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Problem solving and numeracy literacy are essential competencies in 21st-century mathematics education, as they require students to understand, apply, and interpret mathematical concepts in real-world contexts. However, school assessments remain predominantly procedural and have not comprehensively measured these competencies. This study aimed to develop a contextual essay-based test instrument grounded in ethnomathematics to assess senior high school students’ problem solving and numeracy literacy skills. This research employed a research and development (R&D) method, including needs analysis, test blueprint design, item development, expert validation, limited field testing, and item analysis using the Classical Test Theory approach supported by SPSS. The trial involved 28 twelfth-grade students of SMA Negeri 1 Ketapang. The results showed that the instrument demonstrated very high content validity (average 95.31%) and empirical validity, as student responses reflected the indicators of problem solving and numeracy literacy based on the analytic rubric. The reliability coefficients were very high, with Cronbach’s Alpha values of 0.907 for problem solving and 0.918 for numeracy literacy. All items were categorized as having moderate difficulty levels and good to very good discrimination indices. The novelty of this study lies in the simultaneous integration of Polya’s problem-solving stages and the PISA numeracy framework into an empirically validated assessment instrument based on local ethnomathematical contexts. This instrument provides a more contextual and authentic alternative for assessing higher-order thinking skills in mathematics.